Maintenance Management In Handling The Problem of Rail Damage Affecting Railway Travel Safety (Wonokromo-Sidoarjo Route) - Ika Setyorini Pradjojowaty (Publikasi Indonesia, 2025)
Regarding the number of trains that have accidents, one of them is due to damaged rails among 4 other causes, so that it has an impact on the delay and safety of the train journey itself. The purpose of this study is as an input related to the maintenance management system, especially in terms of handling problems of damage to railway infrastructure, in this case rail lines that require maintenance, especially regarding human resources who handle them, so that appropriate solutions can be obtained in short-term or long-term solutions for the comfort and safety of train travel. This study uses a mix method, and when identification is carried out, problems are found on the railway, namely the number of damages where after analysis, the results are a number of maintenance equipment that is still lacking, as well as the number of logistics or spare parts. And after being evaluated, it was found that some damage to the components of the Wonokromo – Sidoarjo cross rail road was caused by the cross load received by the cross of 11,543,796 tons/year, so that when it is associated with PM 60 of 2012 concerning Technical Requirements for Railway Lines, the Wonokromo-Sidoarjo cross should no longer be included in road class III but class II, so that maintenance management is needed in the maintenance of railway infrastructure which should be further improved, especially in terms of fulfilling certified human resources.